GLOBAL WARMING –PRESENT SCENARIO - Singh, Sarvapriya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Global warming is an ongoing phenomenon, and its detrimental effects are already evident. It is severely impacting ecosystems and disrupting ecological balance. Given the alarming consequences of global warming, immediate and effective solutions are essential. This conceptual paper explores the fundamental causes of global warming, emphasizing society’s role in contributing to the crisis. It highlights how increased awareness can empower individuals to change their behavior and influence others toward positive environmental action. The paper examines the progression of global warming, its current and future hazards, and its potential to create increasingly inhospitable living conditions. Furthermore, it proposes practical strategies for mitigating climate change through lifestyle adjustments at the individual, institutional, and societal levels. Finally, it outlines global preventive measures that, if implemented earnestly, can significantly curb global warming.